A Possible Patient Journey: A Tool to Facilitate Patient-Centered Care - Gregory, Melanie (Seminars in Hearing, 2012)
The concept of a patient journey provides a framework for understanding the complex phases and numerous milestones of life with hearing loss from the perspective of the patient. This understanding can facilitate patient-centered care, which has been found to increase patient satisfaction with the clinical encounter, encourage patients to participate in the rehabilitation process, and result in treatment and outcomes that reflect the needs and wishes of the individual. By being curious about the most significant aspects of an individual's journey and understanding the events that trigger action for a patient, the audiologist can engage the patient as joint decision makers in the treatment plan. The Ida Institute developed the Possible Patient Journey tool to assist audiologists in taking the patient's point of view into account. It is one way of illustrating the patient journey and is designed to support clinicians and students in visualizing or “mapping” the patient journey. The journey tool may be used as a starting point for understanding the patient's story. It enables the audiologist to engage the patient and focus on areas of behavior changes that are important to him or her. By understanding the patient journey, audiologists can address the entire patient experience and collaborate with patients to gain better outcomes.
Keywords: Patient journey; patient-centered care; motivational interviewing; mapping tools; A Possible Patient Journey tool